Parosteal Lipoma of Proximal Radius: A Case Report of an Unusual Swelling and Review of Literature - Murugharaj, Shishir (J Orthop Case Rep, 2019)
INTRODUCTION: Lipomas are considered to be benign tumors comprising 50% of all soft tissue tumors. They originate from mesodermal germ layer but are classified based on component tissue and location. Parosteal lipomas are frequently located at the extremities, particularly at diaphysis or diametaphysis of long bones. CASE REPORT: Here, we report a case of parosteal lipoma with a delayed presentation involving dominant right forearm without any neurological deficits to create awareness of the rare existence of this benign tumor. CONCLUSION: A prompt diagnosis of such tumors has to be done as early as possible.